Local ethno-political polarization and election violence in majoritarian vs. proportional systems - Müller-Crepon, C (SAGE Publications, 2021)
How does local ethnic demography affect the conduct of majoritarian elections? Because legislative elections in majoritarian systems are contested locally, local ethno-political polarization increases the risk of pre-election violence. In districts that are polarized between politically competing ethnic groups, violence can be targeted with comparative ease at opposing voters, and can, if perpetrated collectively, mobilize the perpetrators’ co-ethnics. I do not expect such dynamics in PR systems where political competition plays out at higher geographical levels. To test this argument, I combine new data on the ethnic composition of local populations in 22 African countries with monthly data on riots and survey data on campaign violence. Ethno-politically polarized districts in majoritarian and mixed electoral systems see substantively larger increases in the number of riots prior to legislative elections and more fear of pre-election violence among citizens than non-polarized districts in the same country and at the same time. I do not find these patterns in PR systems. The results enhance our understanding of how electoral systems interact with local ethnic demography in shaping pre-election violence.